2008
DOI: 10.1177/1358863x07084910
|View full text |Cite
|
Sign up to set email alerts
|

A randomized trial of iloprost in patients with intermittent claudication

Abstract: Prostanoids, which promote vasodilation and reduce platelet aggregation, have been proposed as candidate therapies for intermittent claudication due to peripheral arterial disease (PAD). However, studies of these medications have yielded inconsistent results. This study tested the hypothesis that iloprost, an oral prostacyclin analogue, would improve walking distance and quality of life in patients with intermittent claudication. The study was a multi-center, randomized, double-blind, placebo-controlled trial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
21
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 38 publications
0
21
0
1
Order By: Relevance
“…117 Although pentoxifylline has been shown to improve symptoms of claudication, the overall benefit is small. 118 Accordingly, pentoxifylline is considered for therapy only in patients who are not able to receive or tolerate cilostazol. 16 …”
Section: Pentoxifyllinementioning
confidence: 99%
“…117 Although pentoxifylline has been shown to improve symptoms of claudication, the overall benefit is small. 118 Accordingly, pentoxifylline is considered for therapy only in patients who are not able to receive or tolerate cilostazol. 16 …”
Section: Pentoxifyllinementioning
confidence: 99%
“…Of the eight trials 34,58,70,71,73,76,77 comparing pentoxifylline versus placebo in terms of MWD, two trials significantly favoured pentoxifylline over placebo: Creager et al (p = 0.039) 70 and Di Perri et al (p < 0.01). 77 Of these, the Di Perri 77 trial did not use a treadmill protocol, instead measuring the distance that a patient could walk on a horizontal level at metronome controlled speed of 120 steps per minute, with a follow-up at 8 weeks.…”
mentioning
confidence: 99%
“…77 Of these, the Di Perri 77 trial did not use a treadmill protocol, instead measuring the distance that a patient could walk on a horizontal level at metronome controlled speed of 120 steps per minute, with a follow-up at 8 weeks. The Creager et al 70 trial used a graded treadmill test protocol, and found a significant effect on MWD at 24 weeks. Of the six trials finding no significant difference between groups for MWD, one of these used the graded test (Dawson et al; 58 p = 0.82) and had a follow-up of 24 weeks.…”
mentioning
confidence: 99%
See 2 more Smart Citations